ANALISIS KESEMPATAN KERJA SEKTOR FORMAL DI INDONESIA - Neka, Diarora Arjuna; Sentosa, Sri Ulfa; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2015)
This study aims to analyze and determine (1) the effect of wages, economic growth, labor productivity, investment, inflation, government spending and government policies (moratorium) on formal employment in Indonesia. This research use descriptive and associative. Analysis this type of data is the documentary data, the data source is a form of secondary data from the 2009 panel - in 2012 in 33 provinces in Indonesia. This study uses panel regression model with common method effect. The research concludes that formal sector employment opportunities in this study is significantly influenced by the wages, economic growth, labor productivity, investment and government spending. While inflation and government policy variables (moratorium) no significant effect on formal employment in Indonesia. This study, economic growth is one of the most well insturmen to increase formal employment opportunities in Indonesia. This is evident from the high number of coefficients to the level of economic growth of formal employment in Indonesia. The trick is to increase incomes through job creation or investment in Indonesia, especially in the real sector. Government needs to set regulations on how and investment requirements are easily accepted by the investors, the guarantee of political stability, security and law enforcement are consistent, providing accurate information to investors in order to promote the area, realizing the mechanism of effective one-stop service for potential investors, as well as increasing the cooperation between the government harmonious, private and public.